2003
DOI: 10.1046/j.1365-313x.2003.01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Arabidopsis colonized by a plant‐growth promoting rhizobacterium reveals a general effect on disease resistance

Abstract: SummaryRNA transcript levels of Arabidopsis plants, infected by the rhizobacterium Pseudomonas thivervalensis (strain MLG45), and axenic control plants were compared using cDNA microarrays representing approximately 14 300 genes. The analysis revealed an increase of defence-related transcripts in the shoots of bacterized plants relative to control (axenic) plants. These modi®cations of transcript levels were con®rmed by physiological experiments. Plants infected with P. thivervalensis were more resistant to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 56 publications
2
68
0
Order By: Relevance
“…In contrast, only 16 to 64 of the genes were shared between Pf.SS101 and other rhizobacteria (Supplemental Fig. S1; Supplemental Table S9; Cartieaux et al, 2003Cartieaux et al, , 2008Verhagen et al, 2004;Wang et al, 2005;Weston et al, 2012). From these data, we conclude that the signal transduction pathways and metabolic changes induced in Arabidopsis by Pf.SS101 do not resemble those induced by many other rhizobacteria studied to date.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast, only 16 to 64 of the genes were shared between Pf.SS101 and other rhizobacteria (Supplemental Fig. S1; Supplemental Table S9; Cartieaux et al, 2003Cartieaux et al, , 2008Verhagen et al, 2004;Wang et al, 2005;Weston et al, 2012). From these data, we conclude that the signal transduction pathways and metabolic changes induced in Arabidopsis by Pf.SS101 do not resemble those induced by many other rhizobacteria studied to date.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, for only few rhizobacterial strains, transcriptomic analyses have been conducted to unravel the molecular changes in plants associated with induced systemic resistance (Cartieaux et al, 2003(Cartieaux et al, , 2008Verhagen et al, 2004;Wang et al, 2005;Weston et al, 2012). Almost all of these microarray studies revealed relatively few transcriptional changes: for instance, plant-growth promoting Pseudomonas thivervalensis strain MLG45 induced transcriptional changes in 63 genes in the shoots and in nine genes in the roots of Arabidopsis (Arabidopsis thaliana), with an increase in defense-related transcripts and a repression of photosynthesis-related genes (Cartieaux et al, 2003). In the transcriptome analysis by Verhagen et al (2004), 97 genes were differentially regulated in the roots upon colonization by Pseudomonas fluorescens strain WCS417r (Pf.WCS417r), but no detectable transcriptional changes were found in the shoots.…”
mentioning
confidence: 99%
“…These results appear to contrast with an analysis of Arabidopsis plants treated with the rhizobacterium Pseudomonas thivervalensis, which likewise induced systemic resistance against Pst (Cartieaux et al, 2003). Those experiments were conducted in Arabidopsis accession Ws-0, which is known to be incapable of expressing ISR (Ton et al, 1999).…”
Section: Expression Of Isrmentioning
confidence: 80%
“…Several other genera of soil bacteria, including Pseudomonas and Bacillus species, can stimulate root proliferation or have antagonistic effects on pathogens in the rhizosphere (Kloepper and Schroth, 1978;Ellis et al, 2000;Whipps, 2001). Contrary to the AM and nodule symbioses, few investigations have focused on the molecular bases of plant responses to rhizobacteria such as Pseudomonas, and studies have mainly been concerned with elucidating the basis of induced systemic resistance by Pseudomonas species in Arabidopsis (Arabidopsis thaliana; Cartieaux et al, 2003;Verhagen et al, 2004;Wang et al, 2005).…”
mentioning
confidence: 99%